Desarrollo de la motricidad fina mediante técnicas grafoplásticas en los niños de 4 años de la Unidad Educativa Francisco Huerta Rendón - Piza Saltos, Damaris Lisbeth (2023)
This research project deals with the development of fine motor skills through graphoplastic techniques in 4-year-old children from the Francisco Huerta Rendón Educational Unit in the city of Babahoyo. In the educational institution it has been shown that some children have motor weaknesses when developing academic activities; Therefore, the objective of the study is to determine the use of graphoplastic techniques in the development of fine motor skills in children. The methodology used in the research was based on a non-experimental design, a qualitative approach and field, documentary and descriptive research; as well as the observation technique with its respective instrument addressed to a sample of 40 4-year-old infants. Among the results that were evidenced are that, the initial boys and girls have problems when carrying out activities with paper and pencil, because when making a stroke they do it with rigidity (lack of elasticity and tonicity of the muscles); In addition, preschoolers apply palmar pressure when holding objects and educators make limited use of graphoplastic techniques, which hinders fine motor development. In conclusion, pedagogical strategies must be implemented effectively so that they contribute to the comprehensive development of children, strengthening their fine motor skills, fostering their creativity, and promoting their active participation in the learning process.